Development of a satellite network simulator tool and simulation of AX.25, FX.25 and a hybrid protocol for nano-satellite communications - Le Roux, Jan-Hielke (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng)--Stellenbosch University, 2014.